Evaluation of toothbrushes higiene and storage by dental students (Research, Society and Development, 2023)
Dental biofilm is controlled and removed through the use of toothbrushes, which aim to promote teeth cleaning and ensure good oral health. However, after use and depending on how it is stored, contamination may occur in its bristles and become a source of disease transmission. Thus, the objective of this work was to carry out a study on the conditions of storage and hygiene of the toothbrushes of the Dentistry students of the University Center of Viçosa, as well as the microorganisms present in them. Participating students donated their toothbrushes and filled out a form, toothbrushes were subsequently subjected to microbiological analysis. Then, the microbiological results were compared with the students' responses and the relationship between the conditions of use and the storage location with the microorganisms present in the bristles of the brushes was proven. Thus, it was observed that the students' toothbrushes were contaminated by different types of bacteria. The correct storage and disinfection of toothbrushes after use are measures that help to promote oral and systemic health, as they influence the presence of microorganisms present in them, knowledge that must be disseminated in the faculties of Dentistry.